Human resource management impact on knowledge management - Evidence from the Portuguese banking sector - Figueiredo, Elisa (2016)
Purpose – The purpose of this paper is to explain and empirically test the dependence of organizational processes related to knowledge on the nature of assumptions operating in processes of human resource management (HRM) in organizations. It concentrates on practices related to training, career development and retention. Design/methodology/approach – This empirical study as a quantitative nature and the sample is made up of 5,306 collaborators in 634 organizations belonging to an economic group in the banking sub-sector. Data were collected through two questionnaires: human resource management practices questionnaire and knowledge management questionnaire – short form. The model was tested by applying univariate and multivariate multiple regression analyses. Findings – Findings provide support for the proposed model and show the predictive capacity of the HRM practices regarding knowledge management (KM) processes, revealing a strong direct relationship between the two constructs. It stands out that the people management practices adopted from an organic and valued perspective possess a particular and distinctive capacity to predict and impact positively on KM processes. Practical implications – The findings may be used by human resources and KM practitioners interested in the development of organizational knowledge through human resource practices. Originality/value – Themain contribution of this study is to confirmthe close relationship of dependency between organizational management processes regarding people and knowledge, showing the positive effect of best practices of HRM on KM processes, as opposed to traditional or transactional practices.